2018
DOI: 10.1038/s41467-018-03777-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased formate overflow is a hallmark of oxidative cancer

Abstract: Formate overflow coupled to mitochondrial oxidative metabolism\ has been observed in cancer cell lines, but whether that takes place in the tumor microenvironment is not known. Here we report the observation of serine catabolism to formate in normal murine tissues, with a relative rate correlating with serine levels and the tissue oxidative state. Yet, serine catabolism to formate is increased in the transformed tissue of in vivo models of intestinal adenomas and mammary carcinomas. The increased serine catabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
137
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(146 citation statements)
references
References 29 publications
9
137
0
Order By: Relevance
“…6B). We also showed that the transformed tissues have a high NAD + /(NAD + +NADH) ratio that is either similar than the normal tissue (Meiser et al, 2018) (Fig. 6C).…”
Section: In Vivo Validation In Mouse Models Of Cancermentioning
confidence: 61%
See 3 more Smart Citations
“…6B). We also showed that the transformed tissues have a high NAD + /(NAD + +NADH) ratio that is either similar than the normal tissue (Meiser et al, 2018) (Fig. 6C).…”
Section: In Vivo Validation In Mouse Models Of Cancermentioning
confidence: 61%
“…To this end we utilized a combination of 13 C-Methanol tracing, quantification of metabolites by LC-MS and metabolic flux analysis. We showed that the relative rate of serine catabolism to formate was increased in the transformed tissues relative to the normal tissues (Meiser et al, 2018) (Fig. 6B).…”
Section: In Vivo Validation In Mouse Models Of Cancermentioning
confidence: 85%
See 2 more Smart Citations
“…For instance, since overflow metabolism is commonly characteristic to both cancer and stem cells, our theory will contribute to understanding the origin of cancer stem cells (38). We also expect that the metabolic behaviours characteristic to cancer such as serine and glycine metabolism (39,40) and the metabolic responses to drugs (23) will be understood by the microeconomics of metabolism.…”
Section: R a F Tmentioning
confidence: 96%